Respuesta :

Answer:

The answer would be 54

Step-by-step explanation:

Let's break this statement into small pieces. Let's start with [tex](-3)^{3}[/tex]. This means [tex]-3 \times -3 \times -3[/tex] which is equal to [tex]-27[/tex] ([tex]-3 \times -3 = 9, 9 \times -3 = -27[/tex]).

Note the following rules

  • [tex]- \times - = +[/tex]
  • [tex]+ \times + = +[/tex]
  • [tex]- \times + = -[/tex]
  • [tex]+ \times - = -[/tex]

Now let's solve the rest of the equation. [tex]-2 \cdot (-3)^{3} = -2 \cdot -27[/tex] (Note [tex]\cdot[/tex] is the same as [tex]\times[/tex]. [tex]= -2 \cdot -27[/tex], [tex]54[/tex]

The answer is [tex]54[/tex]

ACCESS MORE